2022
DOI: 10.1093/brain/awac244
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral organoids containing an AUTS2 missense variant model microcephaly

Abstract: Variants in the AUTS2 gene are associated with a broad spectrum of neurological conditions characterized by intellectual disability, microcephaly, and congenital brain malformations. Here, we use a human cerebral organoid (CO) model to investigate the pathophysiology of a heterozygous de novo missense AUTS2 variant identified in a patient with multiple neurological impairments including primary microcephaly and profound intellectual disability. Proband COs exhibit reduced growth, deficits in neu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 74 publications
0
12
0
Order By: Relevance
“…A previous study demonstrated that a patient with the AUTS2 T534P missense mutation displayed reduced cortical area and ventriculomegaly on MRI and that a human cerebral organoid study indicated that the AUTS2 T534P missense mutation impairs organoid growth 8 . In its mutant organoids, the division of neural progenitor cells, presumably apical RGCs, is reduced compared to controls during the early neurogenic phase 8 . These suggest that cerebral organoids with AUTS2 missense mutation can reproduce the microcephaly of the AUTS2 syndrome and that AUTS2 may have some roles in neurogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study demonstrated that a patient with the AUTS2 T534P missense mutation displayed reduced cortical area and ventriculomegaly on MRI and that a human cerebral organoid study indicated that the AUTS2 T534P missense mutation impairs organoid growth 8 . In its mutant organoids, the division of neural progenitor cells, presumably apical RGCs, is reduced compared to controls during the early neurogenic phase 8 . These suggest that cerebral organoids with AUTS2 missense mutation can reproduce the microcephaly of the AUTS2 syndrome and that AUTS2 may have some roles in neurogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several common pathological features have been reported frequently in the AUTS2 syndrome, particularly that 65% of the patients present with microcephaly 4,6,7 . Recently, magnetic resonance imaging (MRI) analysis has reported cortical volume loss, cerebellar hypoplasia, and corpus callosum (CC) hypoplasia in patients with AUTS2 syndrome 8,9 . Auts2 -deficient mice show behavioral abnormalities that mimic some of the human symptoms, such as impaired memory and learning and social behavior 1013 .…”
Section: Introductionmentioning
confidence: 99%
“…Brain organoids have helped reveal the mechanisms of microcephaly and illuminated the surprising roles of centrosomes and primary cilia in regulating neurogenesis. Brain organoids derived from microcephaly patients with mutations in centrosome-associated genes such as CDK5RAP2 showed premature neuronal differentiation and a smaller size ( 13 , 22 , 24 , 26 ). Gabriel et al ( 19 ) developed iPS-derived organoids which harbored a splice-site mutation in CPAP and observed longer cilia, retarded cilium disassembly, and delayed cell cycle re-entry leading to premature differentiation of NPCs.…”
Section: Modeling Congenital Brain Malformations Using Organoidsmentioning
confidence: 99%
“…Auts2 -deficient mice feature hyperactivation of excitatory synapses and display behavioral and cognitive changes which partially mirror symptoms observed in human autistic patients ( Hori et al, 2015 ), providing a strong link between AUTS2 and ASD. Transcriptomic data from acutely isolated human tissue showed strong expression of AUTS2 in neurons as well as in astrocytes ( Zhang et al, 2016 ; Karlsson et al, 2021 ), in human cerebral organoids, AUTS2 is expressed in excitatory neurons, radial glia and intermediate progenitors ( Fair et al, 2022 ). Heterozygous de novo missense mutation in AUTS2 detected in ASD patients alters the cell cycle dynamics of neural progenitors, which could hint at the mechanism by which this gene may contribute to the regulation of brain size ( Fair et al, 2022 ).…”
Section: Genetic Changes That Link Brain Evolution Schizophrenia and ...mentioning
confidence: 99%
“…Transcriptomic data from acutely isolated human tissue showed strong expression of AUTS2 in neurons as well as in astrocytes ( Zhang et al, 2016 ; Karlsson et al, 2021 ), in human cerebral organoids, AUTS2 is expressed in excitatory neurons, radial glia and intermediate progenitors ( Fair et al, 2022 ). Heterozygous de novo missense mutation in AUTS2 detected in ASD patients alters the cell cycle dynamics of neural progenitors, which could hint at the mechanism by which this gene may contribute to the regulation of brain size ( Fair et al, 2022 ). In humans, there are two major protein isoforms of AUTS2 ( Biel et al, 2022 ).…”
Section: Genetic Changes That Link Brain Evolution Schizophrenia and ...mentioning
confidence: 99%